Study of genetic diversity using molecular markers in sunflower (Helianthus annuus) - DHUTMAL, RAJESH; MALOO, SHIV RATAN; MORE, A W; SHARMA, VIJAY; ANU; SINGH, VIVEK K (The Indian Journal of Agricultural Sciences, 2021)
Considering the significance of sunflower (Helianthus annuus L.) cultivation under diverse agro-climatic conditions, present study was done to recognize assorted parental lines utilizing RAPD and ISSR markers to lessen environmental effects or test blunders at Rajasthan College of Agriculture, MPUA & T, Udaipur, Rajasthan during 2016. In the present study, RAPD primers produced 334 polymorphic band and ISSR primers produced 160 polymorphic bands. RAPD primers detected more polymorphic loci (56.88%) than the ISSR primers (52.24%). The dendrograms constructed by RAPD, ISSR primers and pooled data were associated with each other, indicating the efficacy of both marker systems in genetic diversity study of sunflower. Based on RAPD, ISSR and pooled data analysis, the restorer line EC 623023, R 16 and seed parental line CMS 234B, PET 2-7-1B were found to be genetically most diverse and fall into different groups. Therefore, their genetic origin seems to be different and could be efficiently used in sunflower breeding programs.